2020
DOI: 10.1021/acs.chemmater.0c00428
|View full text |Cite
|
Sign up to set email alerts
|

High Amino Acid Lattice Loading at Nonambient Conditions Causes Changes in Structure and Expansion Coefficient of Calcite

Abstract: Biogenic crystals produced by organisms have been known for several decades to exhibit intracrystalline organic macromolecules. Here, using a reductionist approach, we tackle the question of whether the incorporation of single amino acids is driven by kinetics or by thermodynamics. We show that when calcite is grown in the presence of amino acids under nonambient conditions, extremely high loading levels of up to 6.12 mol % of aspartic acid (Asp) are achieved. This incorporation leads to marked changes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 18 publications
(51 citation statements)
references
References 57 publications
9
41
0
Order By: Relevance
“…Interestingly, calcite-GlcA crystals exhibited the elongated scalenohedral-like morphology (Figure 1c) resembling that observed for calcite crystals containing high amounts of incorporated amino acids, in particular aspartic acid. [23] As also seen in Figure 1, calcite-GalA crystals reached a size of about 1 mm, whereas calcite-GlcA crystals were about 100 µm in size. These first observations indirectly indicated that MSs probably become incorporated into the lattice of calcite crystals.…”
Section: Resultssupporting
confidence: 62%
See 4 more Smart Citations
“…Interestingly, calcite-GlcA crystals exhibited the elongated scalenohedral-like morphology (Figure 1c) resembling that observed for calcite crystals containing high amounts of incorporated amino acids, in particular aspartic acid. [23] As also seen in Figure 1, calcite-GalA crystals reached a size of about 1 mm, whereas calcite-GlcA crystals were about 100 µm in size. These first observations indirectly indicated that MSs probably become incorporated into the lattice of calcite crystals.…”
Section: Resultssupporting
confidence: 62%
“…Previous reports on biogenic and synthetic calcite crystals containing organic inclusions have clearly verified the concept of a direct correlation between the magnitude of induced lattice distortions and the amount of incorporated organics. [21][22][23] We may therefore conclude that also in the present case, the MS concentrations within crystals displaying larger lattice distortions clearly exceed 1 wt%.…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations